2022
DOI: 10.1186/s12903-022-02584-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of immunologically detectable T-cell sensitization, Immunohistochemical detection of pro-inflammatory cytokines, and clinical parameters of patients after allogeneic intraoral bone grafting procedures: a prospective randomized controlled clinical trial in humans

Abstract: Background The null hypotheses were tested that intraoral bone augmentation using two different allogeneic materials has no impact on the patient’s blood levels of material-specific lymphocytes and on the immunohistochemical detection of pro-inflammatory cytokines IL-1α, IL1ß and TNF-α and T-cell markers CD4, CD8 in biopsies of the test groups. Methods In this prospective RCT, 60 systemically healthy participants were randomly assigned to two allog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…83 Although these patients required some additional horizontal augmentation at time of implant placement, they showed no other clinical differences from the rest of the patients; the study results also raised the possibility that grafts prepared from multiple donors might be more likely to result in such immunological incompatibility than grafts prepared from single donor. 83 It has also been reported that bone grafts, when in contact with major nerves, may act as an irritant and lead to neurosensory complications. 84…”
Section: Late Post-operative Complications (4 Weeks To Implant Placem...mentioning
confidence: 74%
See 1 more Smart Citation
“…83 Although these patients required some additional horizontal augmentation at time of implant placement, they showed no other clinical differences from the rest of the patients; the study results also raised the possibility that grafts prepared from multiple donors might be more likely to result in such immunological incompatibility than grafts prepared from single donor. 83 It has also been reported that bone grafts, when in contact with major nerves, may act as an irritant and lead to neurosensory complications. 84…”
Section: Late Post-operative Complications (4 Weeks To Implant Placem...mentioning
confidence: 74%
“…Recent evidence suggests that, in a few patients (<10% of those receiving the materials), certain bone allografts could elicit immunological responses, which were detected 4 months postoperatively; the patients who developed positive reactions after the grafting procedure showed significantly increased levels of IL‐1α, IL‐1β, and TNF‐α in biopsies, delayed wound healing after the grafting procedure, and greater resorption of the grafted material, which was confirmed at time of implant placement 83 . Although these patients required some additional horizontal augmentation at time of implant placement, they showed no other clinical differences from the rest of the patients; the study results also raised the possibility that grafts prepared from multiple donors might be more likely to result in such immunological incompatibility than grafts prepared from single donor 83 . It has also been reported that bone grafts, when in contact with major nerves, may act as an irritant and lead to neurosensory complications 84 …”
Section: Complications By Biomaterials Typementioning
confidence: 92%